PENGARUH KINERJA KEUANGAN TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 PERIODE 2007-2011 - RUTHINAYA, ALIFA (Jurnal Akuntansi AKUNESA, 2012)
The study was conducted to determine the effect of the financial performance of companies on the disclosure of social responsibility is more widely. Financial performance was measured using the Economic Value Added (EVA). Sampling method using a purposive sampling method. There are eleven companies which become sampel of this study continuously listed in the index LQ45 in the Indonesia Stock Exchange (BEI), which has the financial and corporate social responsibility reports are complete and a row over the period 2007-2011.The results showed that the Economic Value Added (EVA) effect on corporate social responsibility disclosure. Company managed to maximize the economic value-added means the company can reduce the level of risk and tend to report on corporate social responsibility is widely. Key words: Economic Value Added (EVA), Corporate Social Responsibilty (CSR), Indeks LQ45